The PD-1/PD-L1 axis contributes to immune metabolic dysfunctions of monocytes in chronic lymphocytic leukemia - Qorraj, M.; Bruns, Heiko; Böttcher, Martin; Weigand, L.; Saul, D.; Mackensen, Andreas; Jitschin, R.; Mougiakakos, Dimitrios (Leukemia, 2016)
Immune dysfunctions in chronic lymphocytic leukemia (CLL) contribute to tumor immune escape and attenuate immune-based therapies. Monocytes/macrophages represent key components of cancer immune surveillance and effectors for antibody-mediated antitumor effects. Monocytes display an altered subset composition in CLL. Moreover, we find a changed metabolic phenotype: glucose uptake, glucose transporters and expression of glycolytic molecules are reduced. Our data establish a link between glycolytic competence and monocyte-mediated phagocytosis of tumor cells. Furthermore, we report that CLL monocytes express Bruton's tyrosine kinase (BTK). Our observations suggest that using BTK inhibitors in CLL might further aggravate the observed immune metabolic defects in monocytes. Triggering the programmed cell death-1 (PD-1) checkpoint on monocytes hampers glycolysis, phagocytosis and BTK signaling. Conversely, disrupting PD-1/PD-L1 signaling reverses these immune metabolic dysfunctions. Taken together, our findings imply a novel metabolic interplay between CLL cells and monocytes and that blocking PD-1/PD-L1 might restore metabolic together with antitumor activity of CLL monocytes/macrophages.Leukemia advance online publication, 2 September 2016; doi:10.1038/leu.2016.21
EVALuna2:25756